2022
DOI: 10.3390/healthcare10091769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbonated Thickened Drinks on Pharyngeal Swallowing with a Flexible Endoscopic Evaluation of Swallowing in Older Patients with Oropharyngeal Dysphagia

Abstract: This study aimed to determine the efficacy of carbonated and sweetened drinks added to thickened liquids, which are routinely used for patients with dysphagia to improve dysphagia. Patients swallowed thin liquid (Thin), thickened liquid (Thick), carbonated thin drink (C-Thin), and carbonated thickened drink (C-Thick) in random order. Penetration and/or aspiration were scored using the Penetration–Aspiration Scale (PAS). The residue was scored using the Yale Pharyngeal Residue Severity Rating Scale (YPR-SRS). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Saiki et al 338) concluded that CTL cola was more beneficial for dysphagia patients than NTCL. Similar conclusions were reported [339][340][341] . CTL was reported to reduce the risk of aspiration even for dementia patients with Lewy bodies and Parkinson's disease 342) .…”
Section: Effects Of Chemical Sensessupporting
confidence: 91%
“…Saiki et al 338) concluded that CTL cola was more beneficial for dysphagia patients than NTCL. Similar conclusions were reported [339][340][341] . CTL was reported to reduce the risk of aspiration even for dementia patients with Lewy bodies and Parkinson's disease 342) .…”
Section: Effects Of Chemical Sensessupporting
confidence: 91%
“…Carbonated liquids improve swallowing, which may prevent penetration and aspiration 16 . The effect of thickened carbonated beverages on swallowing dynamics has been verified in previous studies 17 . However, the effects of carbonation in commercially available thickened carbonated beverages have not been explored.…”
supporting
confidence: 66%
“…Different studies administered different volumes of CTL to participants, i.e., Bulow et al [ 13 ] used 5 mL sips, Sdvarou et al [ 11 ] used incrementing volumes up to 25 mL, whereas Turkington et al [ 15 ] and Morishita et al [ 10 ] did not use measured volumes but participants were required to take discrete non-measured sips on demand, or as much as they could in one mouthful. The VF assessment also varied between studies with Sdravou et al [ 11 ], Bulow et al [ 12 ] and Turkington et al [ 15 ] using 25 frames/s, Jennings et al [ 14 ] and not commenting on details of VF frame speed and Larsson et al [ 13 ] using a frame speed of only 16 frames/s which makes it possible that their results are less accurate by possibly missing some aspiration between frames.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies administered different volumes of CTL to participants, i.e., Bulow et al [ 13 ] used 5 mL sips, Sdvarou et al [ 11 ] used incrementing volumes up to 25 mL, whereas Turkington et al [ 15 ] and Morishita et al [ 10 ] did not use measured volumes but participants were required to take discrete non-measured sips on demand, or as much as they could in one mouthful. The VF assessment also varied between studies with Sdravou et al [ 11 ], Bulow et al [ 12 ] and Turkington et al [ 15 ] using 25 frames/s, Jennings et al [ 14 ] and not commenting on details of VF frame speed and Larsson et al [ 13 ] using a frame speed of only 16 frames/s which makes it possible that their results are less accurate by possibly missing some aspiration between frames. Whilst the studies focused on participants with neurogenic dysphagia and dysphagia following surgery, participants had a range of neurological diagnoses across the studies which may have affected results, and some of the participants in the studies by Bulow et al [ 13 ] and Morishita et al [ 10 ] did not actually have any neurological impairment, with the most common aetiology of dysphagia in the study by Morishita et al [ 10 ] being deconditioning.…”
Section: Discussionmentioning
confidence: 99%